Developing and Evaluating a New Preclinical Curriculum with Focus on Prevention in Dentistry - Ina M. Schüler; Katharina Bach; Pauline Schädlich; Ute Rabe (Dentistry Journal)
Background/Objectives: New licensing regulations for dentists in Germany offered the opportunity to modernize the dental curriculum regarding content, methodology and structure. This paper aims to evaluate the newly requested preclinical curriculum “Dental Propaedeutic—Focus on Prevention” by dental students and dental educators and to describe the process of development. Methods: The curriculum was developed according to the Kern cycle and the National Competence-Based Learning Objectives Catalog for Dentistry. Lesson planning was based on Bloom’s taxonomy and the taxonomy of significant learning, according to the principle of constructive alignment. A variety of evidence-based teaching methods were implemented. For evaluation, dental students answered a written questionnaire, graded eight topics and added free text. Dental educators were interviewed. Results: Thirty out of fifty-four dental students’ enrolled in the third semester participated in the survey, giving the highest grades to the learning atmosphere. All dental educators involved in the delivery of the curriculum participated in the interview. Dental students and educators expressed satisfaction with this comprehensive teaching approach of prevention in an early stage of the dental curriculum. Dental educators reflected on the high workload for development but valued the opportunity to participate in an evidence-based development process and to introduce various modern teaching and examination methods. Conclusions: The expenditure of time for the development, performance and examination was high. In order to perform 240 teaching units for eight ECTS credits, 419 h of conceptualization/preparation and 344 h for examination had to be invested. This paper might help to facilitate better understanding of the chances and efforts accompanied by curricular changes.